Taphonomy of ammonoid nuclei from the Turonian-Coniacian (Upper Cretaceous) of a Tanzania drilling project core: implications for ammonoid dispersal - Ifrim, Christina; Wendler, Ines; Lehmann, Jens (Cretaceous research, 2018)
Microfossil analyses of samples of upper Turonian to Coniacian (Upper Cretaceous) sedimentary rocks from Tanzania Drilling Project site 31 have documented ammonoid nuclei (earliest whorls). In spite of the limited number of morphological characters, some Lytoceratina (including the heteromorph Turrilitoidea) could be identified at the family level or, in some cases, to genus. Specimens range in diameter between 0.60 and 2.50 mm and thus fall within the size range of previously recorded nuclei. Their absence from the lower part of the core is not a preservational matter, as can be seen from abundant delicate, aragonitic microfossils in this part of the succession. Rather, in analogy to the distribution of paralarvae of extant coleoids, a link between the distribution of juvenile ammonoids and oceanic currents issuing from locally restricted areas of mating and spawning appears more plausible. Our assemblage is one of the few direct indications of marked early juvenile mortality as implied by the high-fecundity reproductive strategy often attributed to ammonoids and at the same time provides an explanation for the paucity of this phenomenon in the fossil record.